Maternal health surveillance panel: a tool for expanding epidemiological surveillance of women's health and its determinants - Rosa Maria Soares Madeira Domingues; Agatha Sacramento Rodrigues; Marcos Augusto Bastos Dias; Valeria Saraceni; Rossana Pulcineli Vieira Francisco; Rejane Sobrinho Pinheiro; Claudia Medina Coeli (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2024)
ABSTRACT Objective: To present the methodology used in the development of two products for maternal health surveillance and its determinants and discuss their possible uses. Methods: Based on a theoretical model of the determinants of maternal death and databases of Brazilian health information systems, two free products were developed: an interactive panel "surveillance of maternal health" and an educational material "Aparecida: a story about the vulnerability of Brazilian women to maternal death", both available on the website of the Brazilian Obstetric Observatory. Results: More than 30 indicators were calculated for the period 2012-2020, containing information on socioeconomic conditions and access to health services, reproductive planning, prenatal care, delivery care, conditions of birth and maternal mortality and morbidity. The indicators related to severe maternal morbidity in public hospitalizations stand out, calculated for the first time for the country. The panel allows analysis by municipality or aggregated by health region, state, macro-region and country; historical series analysis; and comparisons across locations and with benchmarks. Information quality data are presented and discussed in an integrated manner with the indicators. In the educational material, visualizations with national and international data are presented, aiming to help in the understanding of the determinants of maternal death and facilitate the interpretation of the indicators. Conclusion: It is expected that the two products have the potential to expand epidemiological surveillance of maternal health and its determinants, contributing to the formulation of health policies and actions that promote women's health and reduce maternal mortality.